ANALYSIS OF ENGLISH LANGUAGE NEEDS FOR ISLAMIC ECONOMIC LAW STUDENTS AT STITNU SAKINAH DHARMASRAYA - Angel Sophia Intan (PT. Jurnal Center Indonesia Publisher, 2025)
This study investigates the English language needs of Islamic Economic Law students at STITNU Sakinah Dharmasraya. In the era of globalization, English proficiency is crucial for academic and professional success, particularly in fields that intersect with global issues, such as Islamic economic law. This research is using a qualitative descriptive approach, the research involved interviews, observations, and data analysis to identify students’ English competencies and challenges. The Findings in this research show that students require strong skills in reading, writing, speaking, and listening, especially to understand international literature, compose academic and legal documents, and participate in global discourse. However, students face major obstacles such as limited vocabulary rela ted to Sharia and economic terminology, and a lack of confidence in speaking due to minimal exposure. Despite these challenges, students demonstrate high motivation to improve their English for academic advancement and career opportunities. The study emphasizes the need for English instruction tailored to the specific demands of Islamic economic law to better prepare students for global competitiveness